86 - THE SUBJECTIVITY IN UEMS SONG FESTIVALS (Fiep Bulletin - online, 2023)
This study reports observations about the accomplishment of the objectives proposed by the "UEMS Song Festival", whose proposal is to stimulate the production of ideas, encourage experimentation and create space for the expression of feelings of undergraduates, graduates, professors and administrative officers from Universidade Estadual de Mato Grosso do Sul (UEMS), by means of literature and music. The methodology used by the Event Coordination to calling applicants was announcing the Festival through placards, on the internet and the locals TV and radio broadcasting. The contestants had to present inedited compositions and authorial poetry, in terms of lyrics, music and performance. Their appraisal followed criteria such as, novelty, melody, arrangement and creativity, among other aspects previewed in the rules. The jury was comprised of representatives from the State institutions that are reference in music and literature. The presentations aimed at providing joy and pleasure to the partakers. They could explore the expressive possibilities of their bodies and minds as a way to achieve movement and health, subjectivity and socialization among all. The event has been evaluated by the audience through written records made on the back of their invitations. Even in a low number, the evaluations received indicate the UEMS Song Festivals have successfully achieved their main goals, which are worth the university artistic talents, lead students to produce quality works, and provide the external audience with the benefits of the aesthetic appreciation.
Keywords: newness; idea; creativity